2008
DOI: 10.1021/jp803800w
|View full text |Cite
|
Sign up to set email alerts
|

Monodispersed Pd Nanoparticles for Acetylene Selective Hydrogenation: Particle Size and Support Effects

Abstract: Monodispersed Pd nanoparticles (8, 11, and 13 nm in diameter) as confirmed by high resolution transmission electron microscopy were prepared via the reverse microemulsion method and deposited on structured supports consisting of carbon nanofibers (CNF) grown on sintered metal fibers (SMF). The CNF/SMF supports were subjected to oxidative treatments to introduce O-functional groups on the CNF surface. These groups were characterized by temperature-programmed decomposition (TPD) and X-ray photoelectron spectrosc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
72
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 111 publications
(76 citation statements)
references
References 48 publications
3
72
0
1
Order By: Relevance
“…Desorption of CO 2 and CO commenced at the same temperature. In comparison to TPD under flowing He which has been carried out previously [16] the peaks observed in UHV-TPD are broader. This could indicate a non-uniform temperature of the sample.…”
Section: Tpd Resultsmentioning
confidence: 64%
See 2 more Smart Citations
“…Desorption of CO 2 and CO commenced at the same temperature. In comparison to TPD under flowing He which has been carried out previously [16] the peaks observed in UHV-TPD are broader. This could indicate a non-uniform temperature of the sample.…”
Section: Tpd Resultsmentioning
confidence: 64%
“…Additionally however, a broad CO peak at around 500-600 K can be observed for the ozone activated sample and two smaller peaks around 600 and 800 K for the H 2 O 2 activated sample. CO formation is usually assigned to the decomposition of phenols, ethers and carbonyls/quinones at high temperature (>800 K) [14,16,17]. However, as referenced in the introduction the interpretation of TPD spectra in the literature is ambiguous.…”
Section: Tpd Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…When ME-derived monodispersed Pd nanoparticles of 8, 11, and 13 nm diameter were used for the size effect studies, TOF reached a constant value at 11 nm (114). Selectivity to ethylene stayed constant independently on the particle size (19,114). Geometric effect allowed explaining this behaviour.…”
Section: Hydrogenation Of Multiple Carbon-carbon Bondsmentioning
confidence: 94%
“…Thus, the active sites involve the relatively large ensembles of Pd surface atoms. Taking into account that the coverage of the surface by carbon is very high, it was suggested that the ensemble (geometric) effect was responsible for the structure sensitivity of this reaction (19,114).…”
Section: Hydrogenation Of Multiple Carbon-carbon Bondsmentioning
confidence: 99%